2020
DOI: 10.1158/1538-7445.am2020-6417
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 6417: LY3410738, a novel inhibitor of mutant IDH1 is more effective than Ivosidenib and potentiates antileukemic activity of standard chemotherapy in preclinical models of acute myeloid leukemia (AML)

Abstract: Acute myeloid leukemia is associated with the abnormal proliferation of myeloid progenitor cells unable to differentiate. Somatic gain-of-function mutations in isocitrate dehydrogenase (IDH) 1 occur in 10% of newly diagnosed AML patients. IDH1 mutations cause intracellular accumulation of the oncometabolite, 2-hydroxyglutarate (2-HG), which results in a hyper-methylation phenotype and a block in differentiation. Inhibitors of IDH1 mutant enzyme reduce levels of 2-HG, which relieves the differentiation block al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…3d, e ). Finally, we found that the structurally unrelated mutant IDH1 inhibitor LY3410738 22 (Fig. 4 ) potently suppressed both (R) -2HG production and cytokine independence in IDH1 R132H/D279N-expressing TF-1 cells (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…3d, e ). Finally, we found that the structurally unrelated mutant IDH1 inhibitor LY3410738 22 (Fig. 4 ) potently suppressed both (R) -2HG production and cytokine independence in IDH1 R132H/D279N-expressing TF-1 cells (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The chemical structure of ivosidenib was retrieved from PubChem (National Center for Biotechnology Information, PubChem Compound Summary for CID71657455, https://pubchem.ncbi.nlm.nih.gov/compound/Ivosidenib , accessed 6 October 2021). The chemical structure of LY3410738 is in the public domain 22 . Protonation states at pH 7.4 and tridimensional geometries were calculated by JChem (version 21.18, www.chemaxon.com ).…”
Section: Methodsmentioning
confidence: 99%
“…While the co‐crystal structure has illustrated the binding pockets of IDH inhibitors, 146 the development of a new IDH inhibitor that binds to a binding pocket distant from secondary site mutations would be a feasible pharmaceutical strategy to overcome acquired resistance for treating IDH‐mutated AML patients. Indeed, LY3410738, a covalent inhibitor that targets IDH1 by binding to Cys269 in the allosteric binding pocket that is distinct from where ivosidenib binds, has demonstrated improved potency and durability compared to ivosidenib both in vitro and in vivo, suggesting its promising potential for clinical use for targeting secondary site mutations on IDH1 and thus overcoming resistance 147,148 …”
Section: Drug Resistance Mechanisms In Amlmentioning
confidence: 99%
“…Indeed, LY3410738, a covalent inhibitor that targets IDH1 by binding to Cys269 in the allosteric binding pocket that is distinct from where ivosidenib binds, has demonstrated improved potency and durability compared to ivosidenib both in vitro and in vivo, suggesting its promising potential for clinical use for targeting secondary site mutations on IDH1 and thus overcoming resistance. 147,148 Acquired modifications that often lead to either reactivation or persistent activation of signaling pathways essential for cell survival following drug treatment have also been commonly observed in drug-resistant AML cells. For the case of patients with FLT3-mutated AML, this type of resistance has been commonly observed in those treated with type 1 inhibitors that target both FLT3-ITD and FLT3-TKD mutations.…”
Section: Intrinsic Mechanisms Of Drug Resistancementioning
confidence: 99%
“…IDH mutations are prone to occur in AML ( 50 , 51 ), and the FDA-approved drugs ivosidenib and enasidenib have been identified as small molecules, targeting IDH1 and IDH2 in AML, respectively. Furthermore, vorasidenib (AG-881) and LY3410738 are under investigation in phase I trials for the treatment of AML patients with IDH1 and/or IDH2 mutation ( 52 , 53 ).…”
Section: Unique Metabolic Properties Of Hematologic Malignanciesmentioning
confidence: 99%